Epistemonikos: a comprehensive database of systematic reviews for health decision-making - Rada, Gabriel; Pérez, Daniel; Araya Quintanilla, Felipe.; Ávila, Camila; Bravo Soto, Gonzalo.; Bravo Jeria, Rocío.; Cánepa, Aldo; Capurro, Daniel; Castro Gutiérrez, Victoria.; Contreras, Valeria; Edwards, Javiera; Faúndez, Jorge; et al. (BioMed Central, 2020)
"Background: Systematic reviews allow health decisions to be informed by the best available research evidence. However, their number is proliferating quickly, and many skills are required to identify all the relevant reviews for a specific question. Methods and findings: We screen 10 bibliographic databases on a daily or weekly basis, to identify systematic reviews relevant for health decision-making. Using a machine-based approach developed for this project we select reviews, which are then validated by a network of more than 1000 collaborators. After screening over 1,400,000 records we have identified more than 300,000 systematic reviews, which are now stored in a single place and accessible through an easy-to-use search engine. This makes Epistemonikos the largest database of its kind. Conclusions: Using a systematic approach, recruiting a broad network of collaborators and implementing automated methods, we developed a one-stop shop for systematic reviews relevant for health decision making."
Keywords: Bibliographic database.; Systematic reviews.; Epistemonikos.; Evidence-based practice.